THE EFFECT OF ISLAMIC SOCIAL REPORTING, BANK SIZE, AND NON-PERFORMING FINANCING ON THE PROFITABILITY OF SHARIA COMMERCIAL BANKS IN INDONESIA - Zia Imam Perdana; Dedi Supiyadi; Erna Herlinawati (Universitas Muhammadiyah Bengkulu, 2026)
This study examines the effect of Islamic Social Reporting (ISR), bank size, and non-performing financing (NPF) on the profitability of Sharia Commercial Banks (BUS) in Indonesia during the post-merger period of 2021–2024. The study employs a quantitative explanatory approach using secondary data obtained from annual reports, sustainability reports, and Islamic banking statistics issued by the Financial Services Authority (OJK). ISR is measured using a disclosure index based on content analysis, while profitability is proxied by return on assets (ROA). The sample consists of 8 Sharia Commercial Banks, resulting in 24 effective observations after incorporating lagged ISR to mitigate potential reverse causality. Panel data regression is conducted using a fixed effects model, as confirmed by specification tests. The results indicate that lagged ISR has a positive and significant effect on ROA, suggesting that improved Islamic social disclosure enhances bank profitability in subsequent periods. Bank size also shows a positive and significant influence on profitability, reflecting the role of scale and operational capacity. In addition, non-performing financing is positively associated with ROA within the fixed effects framework, indicating a short-run risk–return trade-off during the post-merger and post-pandemic recovery period. These findings highlight the strategic importance of Islamic Social Reporting and structural bank characteristics in supporting sustainable profitability in Indonesia’s Islamic banking sector. Keywords : Islamic Social Reporting; Return On Assets; Bank Size; Non-Performing Financing; Sharia Commercial Banks